International Journal of Industrial Chemistry - Zamani, Hassan Ali
The International Journal of Industrial Chemistry (IJIC) is a single-blind peer-reviewed, open access journal that brings together multidisciplinary interests in one journal and is to disseminate information on all aspects of research and development in industrial chemistry. Contributions in the form of research articles and review papers are considered for publication. It is devoted to the publication of contributions in industrial chemistry and chemical engineering researches. It is also devoted to the publication of contributions in all fields of experimental and applied researches including process control, chemical reactor, materials, environmental chemistry, nanochemistry, petrochemistry, catalysts, polymers, coatings, membranes, lubricants, modeling and scale-up procedures. The editors welcome original contributions that have not been published and are not under consideration elsewhere. All accepted contributions will be published free of charge.